Intersectional identities: Food, space and gender in urban Malawi. Issue 4 (1st October 2016) - Riley, Liam; Dodson, Belinda
Abstract: This briefing provides a feminist interpretation of food consumption in Blantyre, Malawi, drawing primarily from participatory group discussions with a variety of residents. In these discussions participants were asked to name foods and then categorise them as rural, urban or both rural and urban, and then as for men, women or children. The result is an extensive list of foods categorised in a way that provides insight into the signification of these foods in constructing and expressing Malawian urban identities in intersecting socio-spatial, gendered, and generational terms. We link the findings to wider discussions about the 'nutritional transition' taking place in urban Africa and show that the food categories that support this linear model of social change – traditional/modern, rural/urban, natural/processed, local/global – do not reflect the reality of hybridised food cultures in Blantyre. Changing diets are far more nuanced and complex than the dietary transition thesis suggests, being intricately bound up with identities and culture, as well as personal preference, economic necessity, and ecological capacity. Whereas economic factors play a central role in conditioning food choice, our focus on urban residents' perceptions of different foods sheds light on the socio-cultural factors that shape urban food systems. This is an important contribution to debates on how to promote sustainable food security in Africa's urbanising communities.